Implementation of e-accounting applications in cloud technology: an accounting process / Fa'izah Ghazi and Nor Hashimah Abdul Wahid - Ghazi, Fa'izah; Abdul Wahid, Nor Hashimah (Fakulti Perakaunan, 2023)
Significant advancements in computer sciences have been observed since the creation of the first mechanical computer by Charles Babbage in the first half of the 19th century and the invention of the first programmable, electronic, general-purpose digital computer in 1945 (6ztilrk & Kula, 202 1). Business functions across various industries have increasingly integrated advanced hardware and software systems, with the accounting sector being no exception. Brabctca and Goagara (2022) suggest that a continuous evolutionary process, characterized by the consistent adoption of new information technologies, has contributed to the development and modernization of the accounting profession.